Promoting Trade Linkages: The Driving Force of Japan-ASEAN Cooperation in Global Value Chains - Anh, Do Thi; Hung, Vo Minh; Tam, Le Thi Thanh (Journal of Posthumanism, 2025)
Japan-ASEAN trade relations have become a cornerstone of economic cooperation in the Indo-Pacific, shaped by strategic interests and growing interdependence. As Japan leverages ASEAN’s expanding production capacity and consumer base, trade has flourished, particularly in manufacturing sectors such as automobiles, electronics, and chemicals. This dynamic partnership is driven not only by market forces but also by structured agreements like the ASEAN-Japan Comprehensive Economic Partnership (AJCEP) and the Regional Comprehensive Economic Partnership (RCEP), which foster trade liberalization and investment collaboration. Key determinants of trade include economic size, geographic proximity, and sectoral complementarities. ASEAN serves as a crucial link in Japan’s global supply chains, providing raw materials and intermediate products while benefiting from Japanese technology and investment. Japanese multinational corporations have strategically integrated ASEAN economies into their production networks, enhancing industrial development and regional connectivity. Beyond economics, this trade relationship carries significant geopolitical weight. Japan sees ASEAN as an essential partner in maintaining regional stability and responding to shifts in global trade dynamics. As supply chains diversify and economic resilience becomes a priority, ASEAN presents Japan with an alternative trade and production network, reducing dependence on other markets. Future collaboration will be shaped by digital transformation, sustainability, and deeper integration, reinforcing ASEAN’s role as a hub for global commerce while maintaining Japan’s leadership in technology and investment. This evolving partnership will continue to drive regional economic cooperation and strategic alignment in an increasingly complex international landscape.